Topical Nanostructured Lipid Carrier Based Hydrogel of Mometasone Furoate for the Treatment of Psoriasis - Kaur, Navjot; Sharma, Kusha; Bedi, Neena (Pharmaceutical Nanotechnology, 2018)
Objective: The aim of the present study was to develop and evaluate nanostructured lipid carrier based topical hydrogel of mometasone furoate for the treatment of psoriasis. Method: Drug loaded NLCs were successfully developed by microemulsion technique. Pseudo ternary phase diagrams were constructed using different combinations of surfactant and co-surfactants to study the microemulsion existence range. Different compositions were selected from the phase diagram showing maximum microemulsion region and were converted into NLCs by dilution in water (1:20). The optimized formulation was characterised for droplet size, zeta potential, entrapment efficiency and morphology was studied using Transmission Electron Microscopy. Ex vivo permeation studies were carried out using Wistar rat skin. The potential of this formulation in treating psoriatic inflammation was studied using imiquimod induced skin inflammation animal model. Results: The optimized formulation (F4) has droplet size of 163.2±0.522 nm, zeta potential - 0.086±0.099 mV and entrapment efficiency of 60.0±0.187%. Transmission electron microscopy confirmed spherical shape of nanostructured lipid carrier. Carbopol 940 was used to convert NLC dispersion into NLC based hydrogel to improve its viscosity for topical administration. Drug permeation studies showed prolonged drug release from the NLC based gel as compared to marketed formulation following Higuchi release kinetics. The skin deposition of MF loaded NLC based hydrogel was found to 2.5 fold higher than marketed formulation with primary skin irritation index of 0.20. In vivo studies showed complete clearance of parakeratosis by treatment with the prepared NLC formulation. Accelerated stability studies signify high robustness scale of optimized formulation under one month storage period. Conclusion: The prepared NLC based formulation has proved to be a promising carrier system for the treatment of psoriasis.
Keywords: Hydrogel